(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2025)
Background: Enterococcus has emerged as one of the important causative agents of urinary tract infection (UTI) in recent years. Their resistance to many antimicrobials has increased in last few decades. Objective: To find out the appropriate antibiotics to treat the patient caused by different species of enterococci. Methods: This cross-sectional observational study was carried out in Armed Forces Institute of Pathology (AFIP) and Combined Military Hospital (CMH), Dhaka Cantonment, Dhaka during the period of December 2022 to May 2023. During this period, a total of 118 enterococci were isolated from urine specimen as a causative agent of UTI. Results: 6130 urine specimens were cultured. 1056 specimens yielded growth of significant bacteria. 118 isolates were confirmed as enterococci (isolation rate11.17%). The mean age was 25.9±8.5 years and female to male ratio was 1.8:1. Maximum resistance was seen against azithromycin (84.7%), followed by tetracycline (72.1%), doxycycline (61.86%), ciprofloxacin (55.1%) and carbapenems (45%). Most sensitive antibiotic was linezolid (resistance rate 0%), followed by vancomycin (resistance rate 4.23%), combination of amoxicillin and clavulanic acid (resistance rate 13.5%), nitrofurantoin (17.8%). Conclusion: According to this study, linezolid was the most effective antibiotic followed by vancomycin, combination of amoxicillin-clavulanic acid and nitrofurantoin. In this study, sensitivity to nitrofurantoin and amoxicillin-clavulanic was quite promising (77.2% and 86.5% respectively). So these two drugs may be included as a first line treatment regime to treat enterococcal UTI. JAFMC Bangladesh, Vol 20, No 2 (December) 2024: 27-29